A Simple Near‐Infrared Fluorescent Probe for the Detection of Peroxynitrite. Issue 12 (9th December 2019) - Wu, Luling; Tian, Xue; Han, Hai‐Hao; Wang, Jie; Groleau, Robin R.; Tosuwan, Paramabhorn; Wannalerse, Boontana; Sedgwick, Adam C.; Bull, Steven D.; He, Xiao‐Peng; James, Tony D.
Abstract: Herein, we report the evaluation and synthesis of a reaction based fluorescent probe DCM‐Bpin for the detection of Peroxynitrite (ONOO−). DCM‐Bpin exhibits selective fluorescence off‐on response for ONOO − over other reactive oxygen species, including H2 O2 . Moreover, DCM‐Bpin is biocompatible and has been used to visualize exogenous ONOO − in HeLa cells. Abstract : Turn on the light : A 50‐fold "turn‐on" fluorescence response at 667 nm was observed for DCM‐Bpin upon the addition of ONOO − (0–27 equiv.) using an excitation wavelength of 560 nm.